Multiple sclerosis in stepsiblings: recurrence risk and ascertainment. Issue 2 (17th January 2006) - Dyment, D A; Yee, I M L; Ebers, G C; Sadovnick, A D
Abstract : Reports implicating specific transmissible agents in multiple sclerosis (MS) susceptibility continue to appear. We therefore re-evaluated MS risk in 687 stepsiblings of 19 746 MS index cases. We found the risk of MS to be indistinguishable from that of the general population after diagnostic verification. These results are coherent with studies of adopted children, half siblings and conjugals, showing no risk attributable to the familial microenvironment. This family based genetic epidemiological approach found no trace of transmissibility other than genetic from one affected individual to another in the high prevalence area of Canada. This adds to existing data showing that the action of environment in influencing MS risk is operative at a population level.